2017
DOI: 10.1111/resp.12985
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Clostridium butyricum CGMCC0313‐1 reduces ovalbumin‐induced allergic airway inflammation in mice

Abstract: C. butyricum reduces OVA-induced allergic airway inflammation in mice and might be an additional or supplementary therapy for allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…However, there has been no appreciable change in asthma mortality rates from 2006 through 2012, and asthma remains a global problem. In 2017, severe asthma was the focus of a wide variety of papers in Respirology ranging from reviews of the current state of severe asthma management and targeted therapies to experimental trials of probiotics for asthma control in murine models …”
Section: Asthmamentioning
confidence: 99%
See 4 more Smart Citations
“…However, there has been no appreciable change in asthma mortality rates from 2006 through 2012, and asthma remains a global problem. In 2017, severe asthma was the focus of a wide variety of papers in Respirology ranging from reviews of the current state of severe asthma management and targeted therapies to experimental trials of probiotics for asthma control in murine models …”
Section: Asthmamentioning
confidence: 99%
“…In 2017, two studies examining the effect of microbiota on airway inflammation were reported in Respirology. Juan et al . demonstrated that oral administration of Clostridium butyricum CGMCC0313‐1 (a specific butyrate‐producing bacterial strain) reduced ovalbumin‐induced allergic airway inflammation in mice.…”
Section: Asthmamentioning
confidence: 99%
See 3 more Smart Citations